2016
DOI: 10.1590/s1980-5764-2016dn1004015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the use of screening tools for evaluating cognitive impairment in patients with Parkinson's disease

Abstract: BackgroundScreening tests have been used for cognitive deficits in Parkinson's disease (PD).ObjectiveThis study compared the Montreal Cognitive Assessment (MoCA) test, the Mini-Mental State Examination (MMSE) and the clock drawing test for this purpose.MethodsA total of 50 patients with PD were selected, 41 (82%) were diagnosed with dementia by the criteria of the Movement Disorder Society. The test Scales for Outcomes in Parkinson's Disease-Cognition (SCOPA-Cog) was used as the gold standard in comparison wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 35 publications
2
12
1
1
Order By: Relevance
“…It is noteworthy that average scores on the Clock Drawing Test were lower than normal, correlating with alterations on the visuospatial/executive section of the MoCA; data to be considered as a way of compensating for the deficiencies of the MMSE in the evaluation of patients with PD. 17 - 19 The present study corroborates the facts documented by many other investigations, showing that the MoCA can detect the presence of cognitive deterioration in patients with PD. This is of paramount importance because the presence of MCI represents a risk factor for subsequent development of dementia and instruments such as the MMSE lack the sensitivity and specificity to detect the condition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is noteworthy that average scores on the Clock Drawing Test were lower than normal, correlating with alterations on the visuospatial/executive section of the MoCA; data to be considered as a way of compensating for the deficiencies of the MMSE in the evaluation of patients with PD. 17 - 19 The present study corroborates the facts documented by many other investigations, showing that the MoCA can detect the presence of cognitive deterioration in patients with PD. This is of paramount importance because the presence of MCI represents a risk factor for subsequent development of dementia and instruments such as the MMSE lack the sensitivity and specificity to detect the condition.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the comparison of the different cognitive areas showed that visuospatial, attention and delayed recall functions were the most relevant, a result in line with other investigations. 16 , 17 These findings suggest that initial cognitive impairment in PD patients occurs in a range of cognitive domains and highlights the importance of a thorough cognitive assessment using a simple but sensitive neuropsychological test. It is noteworthy that average scores on the Clock Drawing Test were lower than normal, correlating with alterations on the visuospatial/executive section of the MoCA; data to be considered as a way of compensating for the deficiencies of the MMSE in the evaluation of patients with PD.…”
Section: Discussionmentioning
confidence: 90%
“…According to Stella and colleagues [14], PD patients showed difficulties in visuospatial organization and visuoconstructive skills in CDT; instead, Saur and colleagues [15] suggested that the patients' poorly performance, characterized specifically by errors in planning of numbers and hands position as well as by the use of postmeridian digits, might suggest more prominent executive deficits rather than visuospatial impairments. In a successive study by Camargo and colleagues [3], PD patients with and without a diagnosis of dementia showed a different performance in CDT. Interestingly, the authors reported that when CDT was used together with MMSE, the level of sensitivity in distinguishing between the two groups increased respect to MMSE alone.…”
Section: Introductionmentioning
confidence: 95%
“…Clock Drawing Test (CDT) [1] is a common, quick and easy-to-apply neuropsychological instrument to assess global cognitive functioning. Indeed, multiple cognitive domains, including language comprehension, numerical knowledge, executive functions, attention, visuospatial abilities and verbal short-term memory [2][3], are implied to solve it. Because of its usefulness in detecting comprehensively significant information about individuals' cognitive functioning, CDT is frequently used by geriatric experts [4] in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation